2017
DOI: 10.1149/2.1091713jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Study of a Pendant Molten Alumina Droplet and Its Application for Thermodynamic Property Measurements of Al-Ir

Abstract: Limited knowledge of the thermodynamic and transport properties of refractory materials in the liquid state remains a key challenge limiting their application. Using alternating current (AC) and direct current (DC) techniques, the electrochemical kinetics of oxygen evolution and metal deposition was investigated in a pendant droplet of molten alumina (Al 2 O 3 ) with three iridium (Ir) electrodes in a thermal imaging furnace. For the first time, the direct electrolytic decomposition of molten Al 2 O 3 to oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…A similar description relates E * C and U (E * C ). Similarly to that described by Nakanishi et al, 12 the relative values of U (E * C ) and U (E * A ) were found to vary with cell geometry, i.e. the relative geometric surface areas of cathode and anode.…”
Section: Decomposition Voltage Measurements-acv Measurements Were Pesupporting
confidence: 78%
See 3 more Smart Citations
“…A similar description relates E * C and U (E * C ). Similarly to that described by Nakanishi et al, 12 the relative values of U (E * C ) and U (E * A ) were found to vary with cell geometry, i.e. the relative geometric surface areas of cathode and anode.…”
Section: Decomposition Voltage Measurements-acv Measurements Were Pesupporting
confidence: 78%
“…• The similarity of peak-splitting features across 2 nd and higher current harmonics with that observed for an Ir anode in molten Al 2 O 3 . 12 • The relative stability of the Ir anode during the short-duration electrolysis The features for the ACV voltammogram for an Ir anode were found to be consistent for all X La 2 O 3 investigated, permitting detection and measurement of the electrochemical reaction potential E * A coinciding with Reaction 6.…”
Section: Acv Measurements For the Anode And Cathode-a Typical Acv Vomentioning
confidence: 87%
See 2 more Smart Citations
“…In this work, a containerless approach with in situ, real-time visualization was used to study the electrochemical properties of molten TiO 2 − SiO 2 − Al 2 O 3 − MgO − CaO slag. Following the pioneering efforts of Nakanishi and Allanore [17], the pendant droplet technique was employed in a modified thermal imaging furnace. Cyclic voltammetry and potentiostatic electrolysis measurements were performed in a three-electrode configuration using iridium metal as working, pseudo-reference and counter electrodes.…”
Section: Introductionmentioning
confidence: 99%